Cloacal Exstrophy with Mature Teratoma: A Rare Association in a Neonate - Patil, Prashant Sadashiv; Kothari, Paras; Gupta, Abhaya; Gupta, Rahul; Kekre, Geeta; Dikshit, Vishesh; Kamble, Ravi (Journal of Neonatal Surgery, 2016)
Cloacal exstrophy is a very rare and complex malformation. We report a neonate of cloacal exstrophy with mature teratoma presenting as a component of exstrophy. To our knowledge this has not been reported in the literature.